PEMBUATAN WEBSITE DESA WISATA CELUK SEBAGAI MEDIA PROMOSI DAN PEMASARAN - Adnyana, I Gede Yudha; Paramitha, A A Istri Ita; Wijaya, I Nyoman Yudi Anggara (LPPM Universitas Flores, 2024)
The utilization of information technology in the tourism sector has become crucial in promoting and managing tourism potential for local economic growth. This study focuses on the development of a tourism village website for Celuk, a village in Gianyar Regency renowned for its gold and silver crafts centre. The website is designed as part of a digital village acceleration program to broaden the exposure of Celuk Village to both domestic and international tourists. Information about tourist attractions, local activities, craft products, and travel packages will be available on this site. The goal is to create an authentic experience for visitors and simultaneously empower the local economy and social community. In line with the creation of the website, there is also the development of modules and the provision of website management training aimed at the Village-Owned Enterprises (BUMDesa) and IT staff of Celuk Village. This initiative is expected to increase village digitalization and support the government in making Indonesian villages more digital. With this innovation, Celuk Village is anticipated to gain greater attention from tourists, ultimately aiding in increasing the income and welfare of the local community.